Prognostic value of perfusion defect volume at dual energy CTA in patients with pulmonary embolism: correlation with CTA obstruction scores, CT parameters of right ventricular dysfunction and adverse clinical outcome - Apfaltrer, Paul; Bachmann, Valentin; Meyer, Mathias; Henzler, Thomas; Grüttner, Joachim; Walter, Thomas; Schönberg, Stefan; Fink, Christian (European journal of radiology, 2012)
PURPOSE: To investigate the prognostic value of perfusion defect volume (PDvol) at dual-energy-CT-angiography (DE-CTA) in patients with acute pulmonary embolism (PE) by correlating PDvol with CTA-obstruction-scores (OS), CT parameters of right-ventricular-dysfunction (RVD), and adverse-clinical-outcome. MATERIALS AND METHODS: DE-CTA of 60 patients (mean age: 65±14.4 years) with PE were analyzed. Iodine maps were generated, and normalized PDvol--defined as volume of perfusion defects/total lung volume--was quantified. Furthermore, established prognostic parameters (Qanadli and Mastora-OS, and CT parameters of RVD) were obtained. CT parameters of RVD--namely the right ventricle/left ventricle (RV/LV) diameter ratio measured on transverse sections (RV/LVtrans), four-chamber views (RV/LV4ch), and RV/LV volume ratios (RV/LVvol)--were assessed. PDvol was correlated with OS, CT parameters of RVD and adverse clinical outcome (defined as the need for intensive care treatment or death). RESULTS: 10 of 60 patients with PE experienced adverse clinical outcome. Patients with adverse clinical outcome showed significantly higher PDvol (35±11% vs. 23±10%, p=0.002), RV/LV ratios (RV/LV4ch 1.46±0.32 vs. 1.18±0.26, p=0.005; RV/LVvol 2.25±1.33 vs. 1.19±0.56, p=0.002) and higher Mastora global scores (52 vs. 13, p=0.02) compared to those without adverse clinical outcome. A weak correlation was observed between PDvol and the Mastora global score (r=0.5; p=0.0003), as well as between PDvol and RV/LV4Ch (r=0.432, p=0.0006). No correlation was found between PDvol and the Qanadli score or the remainder of the RVD-CT parameters. CONCLUSION: The extent of perfusion defects as assessed by DE-CTA correlates with adverse clinical outcome in patients with PE. Therefore, volumetric quantification of perfusion defects at DE-CTA allows the identification of low-risk patients who do not require intensified monitoring and treatment.
Gesehen am 29.06.2018